2009
DOI: 10.1097/bcr.0b013e3181bfb810
|View full text |Cite
|
Sign up to set email alerts
|

To Heal or Not to Heal: Predictive Value of In Vivo Reflectance-Mode Confocal Microscopy in Assessing Healing Course of Human Burn Wounds

Abstract: The purpose of this study was to assess if the healing course of burn wounds of indeterminate depth can be predicted based on serial in vivo reflectance-mode confocal microscopy (RMCM) analysis. Twenty-four patients (mean age, 33.1+/-11.4 years; mean burn size: 6% TBSA) were investigated at 12, 36, and 72 hours after burn of indeterminate depth and retrospectively grouped into healing group (HG: 16 patients) and nonhealing group (NHG: eight patients). Noninjured skin served as controls. The following parameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…9 Among them, in vivo reflectance confocal laser scanning microscopy (CLSM) represents an innovative optical imaging tool for noninvasive evaluation of normal and diseased skin in vivo and in real time. 11,12 Their findings supported the use of CLSM as an adjunctive tool for evaluation and management of burn wounds. 10 Altintas and co-workers have first employed CLSM for evaluation of burn wounds in human volunteers, whereby aspects of microcirculation, inflammation, and histomorphology have been described.…”
Section: Introductionmentioning
confidence: 71%
“…9 Among them, in vivo reflectance confocal laser scanning microscopy (CLSM) represents an innovative optical imaging tool for noninvasive evaluation of normal and diseased skin in vivo and in real time. 11,12 Their findings supported the use of CLSM as an adjunctive tool for evaluation and management of burn wounds. 10 Altintas and co-workers have first employed CLSM for evaluation of burn wounds in human volunteers, whereby aspects of microcirculation, inflammation, and histomorphology have been described.…”
Section: Introductionmentioning
confidence: 71%
“…Moreover the thickness of the basal layer was preserved in the healing group compared to the obliteration of the basal layer in the nonhealing group at 36 h of measurement. The preliminary study showed some important findings and paved way for further research [55]. …”
Section: Discussionmentioning
confidence: 99%
“…Confocal microscopy or confocal laser scanning microscopy (CLSM) is a high‐resolution optical detection technique, which provides the ability to monitor specimens in multiple planes of depth by adjusting a specific focal depth . In confocal microscopy, a point light source is focused onto a very small volume of a sample.…”
Section: Microscopymentioning
confidence: 99%